Development of a STEAM-Based Module to Enhance HOTS (Analytical, Critical, and Creative Thinking) for Pre-service Science Teachers at UNISLA - Santoso, Agus; Mahbubah, Khoiro; Alim, Sendi Faisal (Universitas Islam Negeri (UIN) Mataram, 2025)
The demand for adaptive graduates in the Society 5.0 era necessitates the enhancement of Higher-Order Thinking Skills (HOTS). However, this is constrained by a lack of innovative teaching materials for pre-service science teachers at the Islamic University of Lamongan. This research aims to develop and assess the feasibility and effectiveness of a STEAM-based module designed to improve HOTS (analytical, critical, and creative thinking). Employing a 4D model of Research and Development (R&D), the product was validated by six experts and trialled with 25 students using a one-group pretest/posttest design. Data were analyzed using feasibility percentages and N-Gain scores. The results indicated that the module was declared